2020
DOI: 10.3389/fcell.2020.565355
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA AC010789.1 Promotes Colorectal Cancer Progression by Targeting MicroRNA-432-3p/ZEB1 Axis and the Wnt/β-Catenin Signaling Pathway

Abstract: Accumulating literatures have indicated that long non-coding RNAs (lncRNAs) are crucial molecules in tumor progression in various human cancers, including colorectal cancer (CRC). However, the clinical significance and regulatory mechanism of a vast majority of lncRNAs in CRC remain to be determined. The current study aimed to explore the function and molecular mechanism of lncRNA AC010789.1 in CRC progression. AC010789.1 found to be overexpressed in CRC tissues and cells. High expression of AC010789.1 was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Most of the lncRNAs included in GILncSig were found to be associated with multiple cancers other than GC. The lncRNA, AC010789.1, was reported to promote the progression of colorectal cancer by targeting the microRNA-432-3p/ZEB1 axis and activating the Wnt/β-catenin signaling pathway (25). It has been reported that HOX-lncRNAs have the capacity to influence the carcinogenesis of lung cancer (26).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the lncRNAs included in GILncSig were found to be associated with multiple cancers other than GC. The lncRNA, AC010789.1, was reported to promote the progression of colorectal cancer by targeting the microRNA-432-3p/ZEB1 axis and activating the Wnt/β-catenin signaling pathway (25). It has been reported that HOX-lncRNAs have the capacity to influence the carcinogenesis of lung cancer (26).…”
Section: Discussionmentioning
confidence: 99%
“…Selectively binding miRNAs by lncRNAs contributes to inhibiting their transcription and promoting their degradation and induces EMT of cRc cells (63,72,90). In addition, those lncRNAs also promote the expression of nuclear β-catenin, cyclin d1, c-Myc, N-cadherin, vimentin, cd44, Jun and TcF1 via activating transcription factor and targeting miRNA, such as the lncRNA-ARAP1-AS1/YY1 (63) and lncRNA-Ac010789.1/miR-432-3p/ZEB1 axes (90). circRNAs exhibit specific roles as the sponges of miRNAs (74).…”
Section: Abnormality Of Non-coding Rnas (Ncrnas)mentioning
confidence: 99%
“…LncRNAsact as competing endogenous RNAs (ceRNAs) to be involved inWnt/β-catenin signaling via sponging miRNAs ( 65 , 96 ), for example, lncRNA-PART1 sponging miR-150-5p/miR-520h ( 86 ) and lncRNA-NEAT1 sponging miR-486-5p ( 89 ). Selectively binding miRNAs by lncRNAs contributes to inhibiting their transcription and promoting their degradation and induces EMT of CRC cells ( 63 , 72 , 90 ). In addition, those lncRNAs also promote the expression of nuclear β-catenin, cyclin D1, c-Myc, N-cadherin, vimentin, CD44, Jun and TCF1 via activating transcription factor and targeting miRNA, such as the lncRNA-ARAP1-AS1/YY1 ( 63 ) and lncRNA-AC010789.1/miR-432-3p/ZEB1 axes ( 90 ).…”
Section: Role Of Wnt/β-catenin Signaling In Colorectal Cancer (Crc)mentioning
confidence: 99%
“…LncRNA AK002107 inversely controls miR-140-5p and triggers EMT in OC by targeting TGFBR1 (Tang et al, 2019 ). LncRNA AC010789.1 promotes colorectal cancer progression by targeting the microRNA-432-3p/ZEB1 axis and the Wnt/β-catenin signaling pathway (Duan et al, 2020 ). A study of the BRCA1/2 ceRNA network in OC patients with wild-type BRCA1/2 revealed a novel three-lncRNA signature that could predict both prognosis and chemo-response (Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%